Vida y razonabilidad - Luis Castillo Córdova (Ius Humani. Jornal do direito, 2017)
This paper is intended to explain the constitutional content of fundamental right to live of the unborn human being. Particularly we want to establish if a measure referring to the unborn human live can be reasonable and therefore acceptable. We would try to answer this question through the Constitutional Case EXP. 02005-2009-PA/TC, devoted to analyze the constitutional validity of the State decision allowing the free distribution of the morning after pill. Constitutionality test correctness will be doubly justified, using the theory of conflict between fundamental rights, as well as using the opposite theory that denies that such a conflict between rights could exists.